STRATEGI PACKAGING PRODUK DALAM MENINGKATKAN PERSEPSI KUALITAS DAN MINAT BELI PADA MAKANAN KEBAB AL-BAIK BESUKI SITUBONDO - Hasanah, Ikromatul; Dassucik, Dassucik; Agusti, Agusti (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to explore the product packaging strategy implemented by Kebab Al-Baik in Besuki, Situbondo, in an effort to increase consumer perception of quality and purchasingg interest. The research approachc used is qualitative with a case study method. Data were collected though direct observation, in-depth interviews with business owners and several consumers, and visual documentation of product packaging. The results of the stdy indicate that packaging has an important roole as a brand communication element that is able to shape the perception of product quality in the eyes of consumers. Visual aspect such as design, color, logo, an the use of clean and safe packaging materials give a professional and hygienic impression that strengthens the positive image of the product.